Art Historical Research In Ghana: Reflections On The State And Direction Of Scholarship. Issue 1 (2nd January 2019) - Quarcoopome, Nii O.
Abstract : This essay is my reflections on the history and present state of the art-historical scholarship about Ghanaian art, both indigenous and contemporary. While it highlights the significant milestones achieved over the last century, it also points to the shortcomings that call into question some fundamental assumptions that have long framed the study of the two artistic genres. The paper also addresses the current stagnation in the academic study of the traditional arts. By outlining the separate trajectories of the historical and modern art genres, I seek to identify areas of convergence and alternative paths for future research that will help to foster a meaningful dialog between the two branches of Ghanaian art history.